Antimicrobials Affect the Fat Body Microbiome and Increase the Brown Planthopper Mortality - Shi, Jiateng; Song, Yang; Shentu, Xuping; Yu, Xiaoping (Frontiers in Physiology, 2021)
Symbionts in the abdomen fat body of brown planthopper (BPH) play an important role in the growth and reproduction of their host, Nilaparvata lugens Stål (Hemiptera: Delphacidae). Thus, controlling BPH infection on rice by inhibiting symbionts with antimicrobials is feasible. However, the effect of antimicrobials on the microbiome in the fat body and the relationship between microbial community and mortality have not been fully elucidated. A decrease in the total number of yeast-like symbiotes in the fat body and elevated mortality were observed after exposure to toyocamycin, tebuconazole, and zhongshengmycin. Additionally, we found that the antimicrobials reduced bacterial diversity and increased fungal diversity in the fat body and altered the bacterial and fungal community structure. Although the total absolute abundance of bacteria and fungi decreased after antimicrobial exposure, the absolute abundance of Serratia increased, indicating that Serratia, which was the most dominant in the fat body, is an important symbiont involved in resistance to antimicrobials. After antimicrobial exposure, seven genera, which probably participated in the nutrition and development function of the host, were totally eliminated from the fat body. Overall, our study enriches the knowledge of microbiomes in the fat body of BPH under antimicrobial treatment and the disturbance of symbionts would be further used to help other pesticides to control pests.